Componentes del Nuevo Campo Intelectual de la Educación y la Pedagogía en Venezuela(1994-2000). Components of the New Intellectual Field: Education and Pedagogy in Venezuela (1994-2000) - Antonio Arellano Duque (Arizona State University, 2005)
Esta investigación se inscribe en el campo de las Reformas Escolares e intenta desarrollar el Concepto de Campo Intelectual de la Educación y la Pedagogía como vía para estudiar la aparición de un nuevo horizonte conceptual para pensar la educación y la pedagogía en Venezuela durante los años 1994-1998/1999-2000. Mediante la reconstrucción de un universo temático, a través del análisis de contenido se plantea mostrar los paradigmas relevantes y las tendencias generales de desarrollo. This investigation is inscribed in the field of school reform and proposes to use the concept of Intellectual Field of Education and Pedagogy as a meaningful approach to study educational and pedagogical changes happening in Venezuela during the years 1994- 2000. This study reconstructs thematic universes through content analysis of key documents and discourses about education to identify the relevant paradigms and general tendencies in educational development.